Protective effect of Arthrocnemum indicum ethanolic extract on hypercholesterolemic rats along with antioxidant and antimicrobial activities - Siwar Ghannay; Kaiss Aouadi; Hafedh Hajlaoui; Adel Kadri (Discover Applied Sciences)
Abstract Natural remedies with high pharmacological and preventive attributes can promote health and cure many diseases caused by imbalances in lipid metabolism. Therefore, in this study, the antioxidant activity was carried out towards 2,2-di(4-tert-octylphenyl)-1-picrylhydrazyl (DPPH), ABTS (2,2′-Azinobis-(3-ethylbenzothiazoline-6-sulfonic acid), Ferric Reducing Antioxidant Power (FRAP) assays. The antimicrobial activity was assessed through disc diffusion and microdilution methods. For the anti-hypercholesterolemic activity, eighteen male Wistar rats (200 to 250 g) were divided into three groups: Control rats with only a standard diet (Group 1), hypercholesterolemic rats fed an atherogenic diet (normal food enriched with 1% cholesterol and 0.1% cholic acid) (Group 2) and hypercholesterolemic rats receiving ethanolic Arthrocnemum indicum extract (EAIE) by gavage at a dose of 250 mg/kg (Group 3). Results revealed that EAIE exhibited the highest polyphenolic contents and thus achieved the potent antioxidant activity towards DPPH (IC50 15.00 ± 0.50 µg/mL), ABTS (IC50111.67 ± 1.43 µg/mL), and FRAP (IC50102.00 ± 0.90 µg/mL) assays, together with powerful antibacterial and antifungal activities against tested microorganisms. Treatment with EAIE significantly improved lipid profiles, antioxidant enzyme levels, and reduced oxidative stress markers in hypercholesterolemic rats. Thus, it can be concluded that for good therapeutic approach, EAIE supplements supported by clinical trials and bioavailable formulations could be used into nutraceuticals, functional foods or pharmacognosy to prevent infections and overcome hypercholesterolemia, oxidative stress, atherosclerotic and cardiovascular disease.